KINERJA EKUALISER MENGGUNAKAN ALGORITMA MODULUS KONSTAN DALAM MENDETEKSI ISYARAT DS-CDMA PEMAKAI-JAMAK - Imam Santoso (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
This research presents modified constant modulus algorithm (CMA) with prewithening and minimum entropy measurement to detect the signal of desired user from multiuser Direct Sequence Code Division Multiple Access (DS-CDMA) signals. Themodified CMA detector could blindly adapted or equalized the fading channel caused by multipath without training signal as in the conventional adaptive detectors. Simulation was used to evaluate the detector’s performance. As the results under multipath fading channel with SNR = 20 dB and desired user power –5 dB than the other users, the modified CMA gave the bit error probability 0.031 and this is better than those with the standard CMA, matched filter, and LMS detectors. Keyword: CDMA, channel equalization, CMA.